Review of the formation and influencing factors of food-derived glycated lipids. Issue 13 (20th July 2022) - Han, Lipeng; Lin, Qingna; Liu, Guoqin; Han, Dongxue; Niu, Li
Abstract: Glycated lipids are formed by a Maillard reaction between the aldehyde group of a reducing sugar with the free amino group of an amino-lipid. The formation and accumulation of glycated lipids are closely related to the prognosis of diabetes, vascular disease, and cancer. However, it is not clear whether food-derived glycated lipids pose a direct threat to the human body. In this review, potentially harmful effect, distribution, formation environment and mechanism, and determination and inhibitory methods of glycated lipids are presented. Future research directions for the study of food-derived glycated lipids include: (1) understanding their digestion, absorption, and metabolism in the human body; (2) expanding the available database for associated risk assessment; (3) relating their formation mechanism to food production processes; (4) revealing the formation mechanism of food-derived glycated lipids; (5) developing rapid, reliable, and inexpensive determination methods for the compounds in different foods; and (6) seeking effective inhibitors. This review will contribute to the final control of food-derived glycated lipids.